Highly Flexible Non-Volatile Resistive Memory Devices Based on ZnO Nanoparticle/Graphene Heterostructures Embedded in Poly(methyl methacrylate) - Awasthi S.; Pramanik S.; Singh K.K.; Mohan A.; Pal B.N. (My University, 2025)
Highly flexible, nonvolatile resistive switching-based memory devices with a hierarchical thin-film architecture were fabricated using a low-temperature, cost-efficient solution processing technique. The device structure consists of an ITO-coated flexible PET substrate as the bottom electrode and a PMMA-embedded reduced-graphene/ZnO nanoparticle (NP) (rGO/ZnO NP) heterostructure as the flexible active layer. Besides, a PMMA-embedded graphene oxide (GO/PMMA)-based device was also fabricated as a reference. The operating voltage of this device is limited within ±2 V, whereas the ON/OFF current ratio is ∼106, which is ∼103 times higher than the reference device. The device also exhibited excellent endurance and retention characteristics, with no significant degradation for more than 50 cycles. Besides, the retention time of this device is ∼104 s, which is several times more than that of the reference device. These electrical performance enhancements were attributed to the multifunctionality introduced by the rGO/ZnO NP heterostructures, which combine the excellent conductivity of rGO nanosheets with charge trapping and transport properties and high electron mobility of ZnO nanostructures. A model based on the energy band of the components of this composite material has been proposed for a better understanding of this mechanism. Flexibility studies exhibited stable device performance for an extreme bending radius of 6 mm. The resistance of the device in ON and OFF states did not show any significant change even after 1000 bending cycles, thus establishing the device as an excellent memory candidate for flexible electronic applications such as flexible displays and sensors, wearable devices, implantable medical devices, and portable diagnostic devices. © 2024 American Chemical Society